China : Coping with economic restructuring and labour market adjustments. (International Labour Office, 2011)
China has enjoyed spectacularly high GDP growth rates for over more than three decades, thanks to the massive economic, social and institutional reforms put in place during a period of intensifying globalization.' Based on a study by the Institute for Labour Studies Ministry of Human Resources and Social Security, People's Republic of China, this report provides a unique account of China's move towards increased participation in the market economy and how the Government coped with the massive labour adjustments that came with the restructuring process.